On the evolution of the serotonin transporter linked polymorphic region (5-HTTLPR) in primates - Dobson, Seth D.; Brent, Lauren J. (Frontiers in Human Neuroscience, 2013)
Some allelic variants of the serotonin transporter linked polymorphic region (5-HTTLPR) result in lower levels of expression of the serotonin transporter gene (SLC6A4). These low-expressing (LE) alleles are associated with mental-health disorders in a minority of humans that carry them. Humans are not the only primates that exhibit this polymorphism; other species, including some monkeys, also have LE and high-expressing (HE) variants of 5-HTTLPR. We propose a behavioral genetic framework to explain the adaptive evolution of this polymorphism in primates, including humans. We hypothesize that both LE and HE alleles are maintained by balancing selection in species characterized by short-term fluctuations in social competition levels. More specifically, we propose that LE carriers benefit from their hypervigilant tendencies during periods of elevated competition, whereas HE homozygotes cope best when competition levels do not deviate from the norm. Thus, both alleles have long-term benefits when competition levels tend to vary substantially over relatively short timescales within a social group. We describe this hypothesis in detail and outline a series of predictions to test it. Some of these predictions are supported by findings in the current literature, while others remain areas of future research.